2020
DOI: 10.1136/bmjnph-2019-000053
|View full text |Cite
|
Sign up to set email alerts
|

Food & mood: a review of supplementary prebiotic and probiotic interventions in the treatment of anxiety and depression in adults

Abstract: BackgroundA bidirectional relationship exists between the brain and the gastrointestinal tract. Foods containing bacteria that positively influence the gastrointestinal microbiome are termed, probiotics; compounds that promote the flourishing of these bacteria are termed, prebiotics. Whether microbiome influencing therapies could treat psychiatric conditions, including depression and anxiety, is an area of interest. Presently, no established consensus for such treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 42 publications
0
39
0
2
Order By: Relevance
“…FMT from these patients into germ-free rats induced depression-like behavior such as lack of pleasure and anxiety in the latter, along with increased levels of tryptophan. A meta-analysis of 71 studies published between 2003 and 2019 [ 165 ] further revealed that probiotics and prebiotics can significantly improve symptoms of anxiety and depression compared to untreated or placebo-treated controls and provide additional benefits to patients with other diseases such as irritable bowel syndrome.…”
Section: Psychiatric Diseasesmentioning
confidence: 99%
“…FMT from these patients into germ-free rats induced depression-like behavior such as lack of pleasure and anxiety in the latter, along with increased levels of tryptophan. A meta-analysis of 71 studies published between 2003 and 2019 [ 165 ] further revealed that probiotics and prebiotics can significantly improve symptoms of anxiety and depression compared to untreated or placebo-treated controls and provide additional benefits to patients with other diseases such as irritable bowel syndrome.…”
Section: Psychiatric Diseasesmentioning
confidence: 99%
“…Omega-3 fatty acids have been investigated for their role in anxiety disorders, but results are inconsistent, and data are too sparse to draw conclusions [ 164 , 165 ]. The role of gastrointestinal microbiota has also received attention as a potential mediator linking diet quality to anxiety symptoms [ 166 , 167 , 168 , 169 ]. Meanwhile, anxiety has been significantly correlated with FA (r = 0.483) [ 4 ] which is not surprising given the strong associations between anxiety and SUDs [ 170 ].…”
Section: Other Psychiatric Diagnosesmentioning
confidence: 99%
“…Many independent meta-analyses of randomized, double-blind, placebo-controlled trials that have been conducted over the last two years have reached overlapping conclusions [ 48 , 49 , 50 , 51 , 52 , 53 ]. Probiotics exhibit statistically significant positive effects on the symptoms of depression in humans compared to placebos.…”
Section: Clinical Studies Of Putative Psychobioticsmentioning
confidence: 99%